Hubungan Aktivitas Menghafal Al-Qur’an Dengan Kontrol Diri Siswa di SD IT Ummu Hafidzah Kecamatan Biru-Biru Kabupaten Deli Serdang - Sari, Amelia Puspita; Nasution, Wahyudin Nur; Nasution, Zukipli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is entitled the Relationship between Memorizing the Al-Qur’an and Students Self-Control at SD IT Ummu Hafidzah Biru-biru District, Deli Serdang Regency. This research is motivated by students lack os self control when they are at school, including students not obeying the rules, poor students behavior and bullying of fellow students. This research aims to find out the relationship between memorizing the Al-Qur’an and students self control. The research uses quantitative correlational methods. The tachnique for taking samples is a total sampling technique which uses the entire population as the research sample. The instruments for obtaining data are observation, distributing queationnaires and documentation. The results of the correlation test show that the significance value (2 tailed) is 0,0040,005, which means Ho is rejected and Ha is accepted, which means there is a positive relationship between the activity of memorizing the Al-Qur’an and students self control at SD IT Ummu Hafidzah, Biru-biru District, Deli Serdang Regency. And the Pearson Correlation value is 0,511 which indicates that the correlation level is moderate